Sosialisasi Pemisahan Sampah & Pembuatan Ecobrick Bersama Anak-Anak Kampung Tua Jabi - Wynnie Wynnie; Denny Marini; Cindya Cindya; Frendy Frendy; Erika Charista Laurens; Hanggara Hanggara; Melyanna Melyanna; Felia Stevina; Wandi Wandi; Franky Viky Franklyn (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
The problem of waste has become increasingly on this time. Society and garbage are inseparable because our daily activities constantly produce it especially plastic. Everyone has a responsibility to protect the environment, the easiest step that can be do is dispose of the trash in its place (reduce) and separate the trash according to its type so the trash can be recycled (reused). The community empowerment program is carried out through the socialization of separate the trash into organic and non-organic types and introduced the “Ecobrick” program to the community in Kampung Tua Jabi (RW 04) which is the target for empowerment. The “Ecobrick” program is carried out by inserting plastic into solid bottles, so the plastic doesn’t need to burned, buried, and cause a polutions. Through this program we expect that the community in Kampung Tua Jabi (RW 04) can make these activities as a routine on their daily lives to create a healthier environment and concern for environment sustainability.